MODEL KOLABORASI DALAM PENERAPAN STANDAR NASIONAL PENGASUHAN ANAK DI LKSA DAMAI SEJAHTERA KABUPATEN SANGGAU KALIMANTAN BARAT - Bayu Febriyanto Saputra (Jurnal Ilmiah Kebijakan dan Pelayanan Pekerjaan Sosial (Biyan), 2022)
Social Welfare Institutions (LKS) in providing social welfare services, one of which is the establishment of a Child Welfare Institution (LKSA), which is a professional service institution that is responsible for providing care as a last alternative and services to replace parental functions for neglected children. Indonesia already has a policy that regulates alternative care for children in institutions/agencies, namely the National Standards for Child Care (SNPA). The application of the SNPA has started in LKSAs in Indonesia, one of which is the LKSA in Sanggau Regency, West Kalimantan. This study aims to find out how the collaboration model is in implementing SNPA at the Damai Sejahtera LKSA in Sanggau Regency. The number of LKSAs in Sanggau Regency is nine LKSAs, one of which is the Damai Sejahtera LKSA which has made efforts in implementing the SNPA. However, LKSA Damai Sejahtera has problems in implementing the SNPA. For this reason, a collaboration model between LKSA and stakeholders, such as the Social Service, is needed to support the implementation of the SNPA. This study uses a qualitative approach. The type of research used is action research. Data collection techniques using interviews, documentation studies and Data Validity Checks. Informants were determined by purposive sampling, the number of informants in this study were eight people. The results of the study showed that LKSA Damai Sejahtera experienced problems in implementing the SNPA including fulfilling the basic needs of children, meeting education and health costs and fulfilling the completeness of online school equipment. To overcome the problems of LKSA in implementing SNPA the researcher made an initial model, a proposed model and a final collaboration model.